Analysis of MIKCC−Type MADS-Box Gene Family in Gossypium hirsutum - Su-cheng JIANG; Chao-you PANG; Mei-zhen SONG; Heng-ling WEI; Shu-li FAN; Shu-xun YU (Journal of Integrative Agriculture, 2014)
MIKCC−type MADS-box genes encode transcription factors that are involved in plant developmental control and signal transduction. Few Gossypium hirsutum MADS-box genes have been reported thus far. Recently, the genome of Gossypium raimondii, considering the contributor of the D subgenome to G. hirsutum, was sequenced and provided a valuable resource to identify and analyze multiple MADS-box genes in G. hirsutum. Here we comprehensively analyzed 53 MIKCC−type MADS-box genes, including 34 newly cloned genes. Phylogenetic analysis of these genes with those from Arabidopsis and grapevine showed that the FLC and AGL12 subfamilies were absent in G. hirsutum. Proteins within a gene subfamily tended to share conserved motifs, and large differences occurred among subfamilies. Expression analysis in multiple tissues and floral organs implied differing roles for the subfamilies in G. hirsutum. At nine loci, two or three genes co-occurred, indicating that they came from different subgenomes; these groups had similar expression patterns. The identification of MIKCC−type MADS-box genes in G. hirsutum provides a valuable resource for further research into flowering time, flower development and ovule development in this important crop plant.